2007
DOI: 10.1089/cap.2006.0144
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Transporter Polymorphism (5-HTTLPR) and Citalopram Effectiveness and Side Effects in Children with Depression and/or Anxiety Disorders

Abstract: The 5-HTTLPR ss genotype was associated with a poorer clinical response with regard to depressive symptoms as well with fewer reports of agitation. The 5-HTTLPR polymorphism may be a genetic marker of response to citalopram in children and adolescents with depression and/or anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 47 publications
1
63
0
1
Order By: Relevance
“…Carriers of the s-allele treated with paroxetine exhibit reduced tolerability and higher discontinuation rates compared to l/l homozygotes [10] , and the s-variant was associated with side effects induced by SSRI [11] . Furthermore, the s-allele was shown to identify patients at risk for developing insomnia and agitation with fluoxetine treatment [12] . Other studies reported no association between 5-HTTLPR and adverse effects induced by SSRI [13,14] .…”
Section: Introductionmentioning
confidence: 99%
“…Carriers of the s-allele treated with paroxetine exhibit reduced tolerability and higher discontinuation rates compared to l/l homozygotes [10] , and the s-variant was associated with side effects induced by SSRI [11] . Furthermore, the s-allele was shown to identify patients at risk for developing insomnia and agitation with fluoxetine treatment [12] . Other studies reported no association between 5-HTTLPR and adverse effects induced by SSRI [13,14] .…”
Section: Introductionmentioning
confidence: 99%
“…[23,24] In one study, depressed and anxious youth homozygous for the more functional allele of the serotonin transporter promoter gene are more likely to respond to citalopram. [25] This genotype did not predict response in the TORDIAs, although polymorphisms of the FKBP5 associated with greater glucocorticoid receptor subsensitivity was associated with an increased risk of suicidal events, which were much more common in depressed youth who did not respond to treatment. [26] …”
Section: Pharmacokinetics and Pharmacogeneticsmentioning
confidence: 83%
“…One study of a pharmacological treatment for paediactric anxiety depression has been reported. The study found the S allele of the 5-HTTLPR is associated with poorer response to citalopram in children and adolescents (Kronenberg et al, 2007). Although the mechanism would be quite different, it is plausible that there could be a similar role for genetic factors in response to CBT.…”
Section: Future Directionsmentioning
confidence: 89%